Importance of Colostrum for Calf Health and development: A brief review - Yanuartono Yanuartono; D. Ramandani; A. Nururrozi; S. Indarjulianto (Universitas Bengkulu, 2022)
Colostrum is a form of milk produced by the mammary glands at the end of pregnancy. Passive antibody intake through the Colostrum during the early hours of birth is very important for calf survival. Consumption of high-quality Colostrum could reduce mortality, strengthen immunity, and increase livability of calves. Therefore, calves must ensure their passive immunity by consuming Colostrum as soon as possible after their birth. This paper aims to review the benefits of Colostrum for calf health development.